2005
DOI: 10.1172/jci25455
|View full text |Cite|
|
Sign up to set email alerts
|

Stem cell-ness: a "magic marker" for cancer

Abstract: Transcriptional profiling of patient tumors is a much-heralded advancement in cancer therapy, as it provides the opportunity to identify patients who would benefit from more or less aggressive therapy and thus allows the development of individualized treatment. However, translation of this promise into patient benefit has proven challenging. In this issue of the JCI, Glinsky and colleagues used human and murine models to identify a potential stem cell mRNA signature, based on the hypothesis that tumors with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…The detection of an ALDH1-positive population in TMA cores may be due to an increased self-renewal activity in these tumors. A recent study has shown that a gene expression signature associated with increased self-renewal of normal stem cells is a predictor of poor prognosis (Glinsky et al, 2005;Lahad et al, 2005). In agreement with our findings, previously described molecular signatures of breast cancer associated with a poor prognosis for breast cancer contain one or more ALDH isotypes (Alexe et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The detection of an ALDH1-positive population in TMA cores may be due to an increased self-renewal activity in these tumors. A recent study has shown that a gene expression signature associated with increased self-renewal of normal stem cells is a predictor of poor prognosis (Glinsky et al, 2005;Lahad et al, 2005). In agreement with our findings, previously described molecular signatures of breast cancer associated with a poor prognosis for breast cancer contain one or more ALDH isotypes (Alexe et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This might serve to delineate different differentiation pathways, rather than attribute ‘stemness’ to all positive tumour cells. As stem cell markers have been associated with a more primitive phenotype, tumour cell expression could indicate de‐differentiation, and thus possible increased aggressiveness 65,66 . Whereas haematological malignancies are related to a well‐characterized hierarchy of putative precursor cells, such a structure is only just emerging with regard to epithelial tumours.…”
Section: Discussionmentioning
confidence: 99%
“…So far, tumor markers are associated with differentiated stages of cancer cells, such as the prostate-specific antigen (PSA) (60,61) and CA125 (62), which are prognostic antigens for prostate and ovarian cancer, respectively. An exciting recent study focused on the proto-oncogene Bmi-1 (63,64), which belongs to the polycomb group gene family (65). Bmi-1 plays a primary role in the self-renewal of adult hematopoietic stem cells (66) and neuronal stem cells (67).…”
Section: Current Chemotherapeutics and Cancer Stem Cells: Implicationmentioning
confidence: 99%